Navigating the Hidden Politics of Water Resource Bureaucracies in Indonesia: Mapping Issue-Elements and Alliances - Muhammad Alif K. Sahide; Micah R. Fisher; Nurul Hasfi; Emban Ibnurusyd Mas’ud; Ahsan Yunus; Fatwa Faturachmat; Siti Halimah Larekeng; Ahmad Maryudi (Faculty of Law, Hasanuddin University, 2023)
Water resource politics are often overlooked for jurisdictional perspectives, or difficult to comprehend for the politics unfolding behind the scenes. Using Indonesia as a case study, we synthesized all water-related bureaucracies to generate a list of “Water resource Issue-Elements,” which served as a framework for translating actor-centered power dynamics. The data is based on policies reviewed from 2014 to 2017, coinciding with the beginning of a new presidential administration with heightened interests in water resource management. The study found that while the central coordinating and planning bureaucracies wield the strongest network power, two sectoral bureaucracies hold tremendous influence in guiding water resource management, which unfold under conditions of highly fragmented politics. On the one hand, the Ministry of Environment and Forestry influences water resources through its land management mandate and seeks to enlarge its bureaucratic power beyond state forest boundaries through the concept of watersheds. On the other hand, The Ministry of Public Works and Housing maintains its traditional mandate for managing river basins, wielding large budgets and networks to control information and determine project-related disbursements. As these two bureaucracies shape alliances administering water resources, their delegating responsibilities also refract to regional bureaucracies, shaping a new set of subnational contestations.